Film as Media of Religious Dialogue: The Reception of Three Indonesian Contemporary Films - Latifah, Latifah (Universitas Islam Negeri Raden Mas Said Surakarta, 2016)
The paper examines the audience’s response in consuming of religious representation in three Indonesian contemporary films: Ayat-Ayat Cinta (Verses of Love), 3 Doa 3 Cinta (3 Wishes 3 Loves), and Perempuan Berkalung Sorban (Woman with a Scarf Around her Neck). By examining the audience’s response in media, particularly through electronic delivery, the paper shows that the public dispute of the Islam representation in this film serves as communication media of religious dialogue. The examination of audience’s response on those three films illuminates the various impacts of Islamic film label embedded in their cinematic representation. Islamic film can be a profitable trademark since it gives more reasons to attract audience than entertainment motive does. Representation of religion analogue to religious teaching and practice creates religious film as media for religious dialogue between people, state, the faith communities, and film makers. Keywords:film, representation, religious-dialogue